Cytotoxic T cells swarm by homotypic chemokine signalling - Jorge Luis Galeano Niño; Sophie V Pageon; Szun S Tay; Feyza Colakoglu; Daryan Kempe; Jack Hywood; Jessica K Mazalo; James Cremasco; Matt A Govendir; Laura F Dagley; Kenneth Hsu; Simone Rizzetto; et al. (eLife, 2020)
Cytotoxic T lymphocytes (CTLs) are thought to arrive at target sites either via random search or following signals by other leukocytes. Here, we reveal independent emergent behaviour in CTL populations attacking tumour masses. Primary murine CTLs coordinate their migration in a process reminiscent of the swarming observed in neutrophils. CTLs engaging cognate targets accelerate the recruitment of distant T cells through long-range homotypic signalling, in part mediated via the diffusion of chemokines CCL3 and CCL4. Newly arriving CTLs augment the chemotactic signal, further accelerating mass recruitment in a positive feedback loop. Activated effector human T cells and chimeric antigen receptor (CAR) T cells similarly employ intra-population signalling to drive rapid convergence. Thus, CTLs recognising a cognate target can induce a localised mass response by amplifying the direct recruitment of additional T cells independently of other leukocytes.